A new method for determining the design values of wave-induced hull girder loads acting on ships. (3rd October 2019) - Paik, Jeom Kee; Lee, Dong Hun; Kim, Sang Jin; Thomas, Giles; Ma, Ming
ABSTRACT: This paper presents a new methodology to determine the design values of wave-induced hull girder loads acting on ships. The method is based on probabilistic approaches associated with selected scenarios that represent possible events in terms of the ship's functionality, operation and environment. As illustrative examples, the method is used to determine the design values of wave-induced vertical bending moments for as-built ships (a VLCC class tanker, a 9, 300 TEU containership and a 22, 000 TEU containership) and a hypothetical 25, 000 TEU containership. The probabilities of exceedance for wave loads acting on ships are discussed in association with the design load values determined from classification society rules. It is found that both the class rule method and the present method are in good agreement for the considered example ships. The present methodology can of course be applied to determine other components of design wave loads such as horizontal bending moments and torsional moments.